Knowledge, Attitudes, and Practices Regarding HIV Among the Middle and Lower Socioeconomic Cohort in Karachi, Pakistan - Khan, Aazmeer; Ali, Syeda S.; Khan, Shazeena; Kidwai, Saera S. (British Journal of Healthcare and Medical Research, 2025)
Introduction: Populations in third-world countries such as Pakistan are at higher risk of contracting human immunodeficiency virus (HIV) which may progress to acquired immune deficiency syndrome (AIDS). This is largely due to the public’s gaps in knowledge regarding HIV infection along with fear and contradictory beliefs associated with the disease. This study aimed to assess the knowledge, attitude, and practices regarding HIV/AIDS of the middle and lower socioeconomic cohort in Karachi, Pakistan. Method: A descriptive cross-sectional survey included patients and their attendants in the Out patient clinic of Creek General Hospital Karachi, Pakistan from Oct 2022 to March 2023 .After taking informed consent, the population involved 500 subjects who were surveyed on their knowledge of the HIV infection. Data was collected using convenient sampling, a structurally validated questionnaire to assess the individuals on their level of awareness, attitude, and practice about HIV infection was used . The frequency of responses in agreement, disagreement or otherwise is calculated in percentages by using Statistical Package for the Social Sciences)SPSS 22. Results: A total data of 500 subjects was collected. 18.2 % of the surveyed individuals were illiterate and the rest had received varying degrees of formal education. 75.8% of our participants were aware of HIV infection and over 60% of them believed unprotected sex and reusing contaminated syringes were the main causes of the spread of the infection. 46.8 % of them believed it was dangerous to be in close vicinity to HIV positive individuals while 35.6% held the opinion that infected individuals should be isolated to prevent future infection. Conclusion:While a majority of individuals seemed to possess a moderate level of understanding regarding HIV infection a high proportion of the population still suffered from gaps in knowledge about the disease, its spread, and prevention and held a discriminatory attitude towards individuals infected with HIV. There is a need for mass education in high-risk lower socioeconomic areas to decrease the burden of the disease.